The Structure and Communicative Import of Selected Proverbs in Nzema Language and Culture - Yakub, Mohammed; Wiafe-Akenten, Nana Anima (Journal of Communication and Cultural Trends, 2023)
Adopting an Ethno-pragmatics framework, the current study aims to describe the sentential structures and communicative imports of selected proverbs in Nzema, a Kwa language of Ghana, West Africa. Using data obtained from primary and secondary sources, this study identifies the structural properties of the proverbs by further highlighting structures which contribute to the pragmatic interpretations of these proverbs. The findings revealed that structural properties such as conditional constructions, causative constructions, focus constructions, and simple, compound, and complex-embedded sentences are prevalent in the syntactic manifestation of Nzema proverbs; which make affirmative and negative propositions. Hence, it was observed that these structural features have a significant contribution to determining the pragmatic import of these proverbs, based on the Nzema social norms, values, beliefs, experiences, and cultural worldview. This research also underscores existing postulations that proverbs are ‘multi-layered’ in terms of their interpretations, and they rely heavily on metaphoric representations and contextual use in any situation. Additionally, it was also noted that the oral construction of proverbs in Nzema is grammatically insightful; and thus, provides a window to the syntactic description of the Nzema language.